Attitude Determinant in Entrepreneurship Behavior of Vocational Student's Entrepreneurship Intention - Ludi Wishnu Wardana (Department of Management, Faculty of Economics, Universitas Negeri Malang, 2018)
This present study was aimed at finding out the correlation of emotional intelligence, entrepreneurship self-efficacy, entrepreneurship behavioral attitude and entrepreneurship intention on vocational school students. The data were analyzed using SEM Smart PLS technique. The study revealed that there is a cause and effect correlation of emotional intelligence and entrepreneurship self-efficacy, entrepreneurship behavioral attitude toward entrepreneurship intention on vocational students in Mojokerto regency as described: 1) empirically, emotional intelligence was proven to have no direct influence on entrepreneurship intention, however, it has direct and strong influence on entrepreneurship behavioral attitude, 2) entrepreneurship self-efficacy has direct and strong influence on entrepreneurship behavioral attitude and entrepreneurship intention, and entrepreneurship self-efficacy also has indirect influence  toward the entrepreneurship intention through entrepreneurship behavioral attitude, 3) entrepreneurship behavioral attitude has direct and strong influence toward entrepreneurship intention.